Sztuczna inseminacja nasieniem zmarłego dawcy – wątpliwości natury prawnej i etycznej - Tworkowska-Baraniuk, Anna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Medical progress has allowed to make artificial insemination procedureseven in a few years after the death of the donor semen. Legal problems are created – questions: the nature of the legal issue of semen remaining after the dead man; born legal status as a result of artificial insemination post mortem child – about the origin of marriage that seems to had ceased with the death of a man, and the possibility of to establish paternity semen donor. This article aims to respond to the legal and ethical doubt
Keywords: artificial insemination; death; fertilization after the death of the donor; law of succession